The use of medium-chain triglycerides in patients with cystic fibrosis - V. V. Zarubina; O. V. Vysokolova; M. A. Mukhina; Е. E. Yakushina; Т. N. Kekeeva (Лечащий Врач)
Background. Medium chain triglycerides are absorbed and metabolized faster than long-chain fatty acids, as they bypass the steps necessary for the absorption of long-chain fatty acids. So, they use in various malabsorptive disorders as a source of calories.Objectives. Retrospectively evaluate the clinical effectiveness of nutrition supplements (a fat emulsion consisting of medium chain triglycerides), used by patient with cyctic fibrosis.Materials and methods. 39 children with cyctic fibrosis aged 1-17 years were observed at Morozovskaya Children's Clinical Hospital. WHO-Anthro and WHO-Anthro Plus were used to determine their nutritional status.Results. At the beginning of the study, all patients with cyctic fibrosis had a body mass index < 25th percentile. The median percentile of body mass index was 7,8. 0% of patients had a Z-score body mass index > 0.25,6% of patients had a Z-score body mass index from 0 to –1. 51,3% of patients had a Z-score body mass index from –1 to –2.23% of patients had a Z-score body mass index < -2. At the end of the study, 28% of patients with cyctic fibrosis had a body mass index > 25th percentile. The median percentile of body mass index was 16,1. 18% of patients had a Z-score body mass index > 0.38,4% of patients had a Z-score body mass index from 0 to –1.25,6% of patients had a Z-score body mass index from –1 to –2, 18% of patients had a Z-score body mass index < –2.Conclusion. The use medium chain triglycerides could improve nutritional status and alleviate steatorrhea in patient with cyctic fibrosis.